2019
DOI: 10.1002/arch.21628
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification and analysis of genes encoding cuticular proteins in the endoparasitoid wasp Pteromalus puparum (Hymenoptera: Pteromalidae)

Abstract: The multifunctional insect cuticle serves as the exoskeleton, determines body shape, restricts water loss, provides attachment sites for muscles and internal organs and is a formidable barrier to invaders. It is morphologically divided into three layers, including envelope, epicuticle, and procuticle and is composed of chitin and cuticular proteins (CPs). Annotation of CPs and their cognate genes may help understand the structure and functions of insect cuticles. In this paper, we interrogated the genome of Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Compared with the number of CP genes in genomes of other lepidopteran species, CP genes carried by FAWs are lower than those in the genomes of S. litura, B. mori and M. sexta [12,15,24,30]. The CP gene number is significantly varied across insect species and taxa, ranging from 45 in A. mellifera to 305 in Aedes aegypti [31][32][33]. Interestingly, genomebased analysis revealed that 287 putative CPs were predicted in S. litura, a lepidopteran species closely related to the FAW [12].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Compared with the number of CP genes in genomes of other lepidopteran species, CP genes carried by FAWs are lower than those in the genomes of S. litura, B. mori and M. sexta [12,15,24,30]. The CP gene number is significantly varied across insect species and taxa, ranging from 45 in A. mellifera to 305 in Aedes aegypti [31][32][33]. Interestingly, genomebased analysis revealed that 287 putative CPs were predicted in S. litura, a lepidopteran species closely related to the FAW [12].…”
Section: Discussionmentioning
confidence: 95%
“…Few CP genes were abundant in nearly all life stages, suggesting a significant role in general cuticle synthesis. It was documented that CP genes that displayed the most abundant expression in specific tissue at particular developmental stages played important roles associated with such tissues during specific developmental periods [12,14,24,31,33,34]. Thus, further investigation into unravelling the expression of CP genes between premolt/eclosion and post-molt/eclosion at particular developmental stages and multiple tissues is essential to provide deep insights into the functional perspectives of CPs in FAW.…”
Section: Discussionmentioning
confidence: 99%
“…In the remaining 22 T. molitor serpins except for TmSPI6, we found that they have some or all consensus conserved amino acids in their hinge region. For serpins with inhibitory function, P1 residue in the RCL determines the substrate specificity, which is considered most important in determining the target proteases (Bode & Huber, 1992; Garrett et al, 2009; Wang et al, 2020). We found that 16 T. molitor serpins (TmSPI1, 34, 7‐9, 11, 15‐17, 20, and 22−26)were predicted to be inhibitor proteins because they have a reasonable P1 position (Garrett et al, 2009) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Insect cuticle sclerotization is a very complex biological process; many genes are involved in this process, such as diphenoloxidases, laccases, peroxidases, and so on (Charles, 2010; Andersen, 2012). Collagen proteins are not the primary compositions of insect cuticle; however, transcriptional analysis has revealed the expression of collagens in epidermis of silk worm (Futahashi et al ., 2008) and wasps (Wang et al ., 2019; Zhou et al ., 2019). Co‐expression of peroxidasin and collagen are observed in integument of bees (Falcon et al ., 2019) and Bombyx wing disc during metamorphosis (Ou et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%